Pemberdayaan Ibu-Ibu PKK Kampung Yaugapsa Kabupaten Jayapura Dalam Membentuk Usaha Pembuatan Virgin Coconut Oil (VCO) - Inggrid Nortalia Kailola; Beatrix Irene Sanderina Wanma (Yayasan Literasi Sains Indonesia, 2022)
Yaugapsa Village, Demta Sub-district, Jayapura District, Papua is one of the villages with abundant coconuts. Coconut trees have enormous benefits for human life. Almost all parts of this tree have benefits. All parts of this tree can be used to produce many products, for example, coconut leaves can be used as woven material and brooms; coconut stems can be used for building materials; and coconut fruit can be used as food. One of the products made from coconut that has many health benefits and a high selling value is virgin coconut oil (VCO). This community service program (PKM) aims to increase the knowledge of the member of PKK (family welfare program) in Yaugapsa Village, Demta Sub-district, Jayapura District by providing training on producing VCO which is useful for maintaining family health and as a business opportunity. The method used was interviews, practices, and discussions and followed by 30 mothers. The result of this training activity is that the manufacture of virgin coconut oil (VCO) does not use additional methods. The manufacture of VCO oil only uses coconut milk without the addition of other substances. The result of this activity is that the oil produced is very clear. This tranning provides a lof of information about VCO production whish is new information and knowledge for participants so than it can be an opportunity for businesses to increase family income.